Differentiation of Skull Base Chondrosarcomas, Chordomas, and Metastases: Utility of DWI and Dynamic Contrast-Enhanced Perfusion MR Imaging - Ota, Y.; Liao, E.; Capizzano, A.A.; Baba, A.; Kurokawa, R.; Kurokawa, M.; Srinivasan, A. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Differentiation of skull base tumors, including chondrosarcomas, chordomas, and metastases, on conventional imaging remains a challenge. We aimed to test the utility of DWI and dynamic contrast-enhanced MR imaging for skull base tumors.MATERIALS AND METHODS: Fifty-nine patients with chondrosarcomas, chordomas, or metastases between January 2015 and October 2021 were included in this retrospective study. Pretreatment normalized mean ADC and dynamic contrast-enhanced MR imaging parameters were calculated. The Kruskal-Wallis H test for all tumor types and the Mann-Whitney U test for each pair of tumors were used.RESULTS: Fifteen chondrosarcomas (9 men; median age, 62 years), 14 chordomas (6 men; median age, 47 years), and 30 metastases (11 men; median age, 61 years) were included in this study. Fractional plasma volume helped distinguish all 3 tumor types (P = .003, <.001, and <.001, respectively), whereas the normalized mean ADC was useful in distinguishing chondrosarcomas from chordomas and metastases (P < .001 and P < .001, respectively); fractional volume of extracellular space, in distinguishing chondrosarcomas from metastases (P = .02); and forward volume transfer constant, in distinguishing metastases from chondrosarcomas/chondroma (P = .002 and .002, respectively) using the Kruskal-Wallis H test. The diagnostic performances of fractional plasma volume for each pair of tumors showed areas under curve of 0.86–0.99 (95% CI, 0.70–1.0); the forward volume transfer constant differentiated metastases from chondrosarcomas/chordomas with areas under curve of 0.82 and 0.82 (95% CI, 0.67–0.98), respectively; and the normalized mean ADC distinguished chondrosarcomas from chordomas/metastases with areas under curve of 0.96 and 0.95 (95% CI, 0.88–1.0), respectively.CONCLUSIONS: DWI and dynamic contrast-enhanced MR imaging sequences can be beneficial for differentiating the 3 common skull base tumors.AUCarea under the curveDCE-MR imagingdynamic contrast-enhanced perfusion MR imagingIQRinterquartile rangeKtransforward volume transfer constantVefractional volume of extracellular spaceVpfractional plasma volumenADCmeannormalized mean ADC